Histopathological study of solitary nodules of thyroid - Khadilkar, UN; Maji, P (Kathmandu University Medical Journal, 2009)
Objective: To determine the incidence of various thyroid disorders manifesting as Solitary Thyroid Nodule and also to evaluate the histomorphology of the lesions. Materials and methods: Hundred specimens of Solitary Thyroid Nodules were studied for gross characteristics, microscopic features, age and sex incidence. Results: Of the 100 cases of Solitary Thyroid Nodules, 66% were non neoplastic and 34% were neoplastic. Among the neoplasms, 21% were malignant and 13% were benign. The age incidence ranged from 20-50 years for non neoplastic lesions and 20-40 years for neoplasms. A female preponderance was seen for both non neoplastic and neoplastic conditions. The solitary nodules involved the right side of the thyroid more commonly than the left. Involutional colloid nodule was the predominant type of solitary nodule (52%). Among the malignant neoplasms, papillary carcinoma was the commonest solitary nodule (13%). One case each of hyalinising trabecular adenoma, columnar cell variant of papillary carcinoma and medullary carcinoma unusually presenting as solitary nodules were encountered in the present study. Conclusion: Histomorphologic evaluation of Solitary Thyroid Nodules presenting without a background setting of multinodular goiter is challenging and mandatory as the diagnoses ranges from the common non neoplastic lesions like involuting nodules to the rare neoplastic conditions like medullary carcinoma. Key words: Solitary Thyroid Nodule morphology, involuting nodule, medullary carcinoma doi: 10.3126/kumj.v6i4.1740   Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 486-490